lncRNAs Functioned as ceRNA to Sponge miR-15a-5p Affects the Prognosis of Pancreatic Adenocarcinoma and Correlates With Tumor Immune Infiltration - Wang, Yu; Wang, Zhen; Li, KaiQiang; Xiang, WeiLing; Chen, BinYu; Jin, LiQin; Hao, Ke (Frontiers in Genetics, 2022)
Pancreatic adenocarcinoma(PAAD) is one of the most common malignant tumors with a poor prognosis worldwide. Mounting evidence suggests that the expression of lncRNAs and the infiltration of immune cells have prognostic value for patients with PAAD. We used GENE EXPRESSION OMNIBUS(GEO)database and identified six genes (COL1A2, ITGA2, ITGB6, LAMA3, LAMB3, LAMC2) that could affect the survival rate of Pancreatic adenocarcinoma patients. Based on a series of in silico analyses for reverse prediction of target genes associated with the prognosis of PAAD, a ceRNA network of mRNA (COL1A2, ITGA2, LAMA3, LAMB3, LAMC2)-microRNA (miR-15a-5p)-long non-coding RNA (LINC00511, LINC01578, PVT1, TNFRSF14-AS1) was constructed. We used the algorithm “CIBERSORT” to assess the proportion of immune cells and found three OS-associated immune cells (Monocytes, Macrophages M1, and Mast cell resting). Moreover, OS-associated genes level was significantly positively associated with immune checkpoint expression and biomarkers of immune cells. In summary, our results clarified that ncRNAs-mediated upregulation of OS-associated genes, and tumor-infiltration immune cells (Monocytes, Macrophages M1, and Mast cell resting) correlated with poor prognosis in PAAD.